2012
DOI: 10.1007/s12070-011-0456-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Adult Recurrent Respiratory Papillomatosis with Oral Acyclovir Following Micro Laryngeal Surgery: A Case Series

Abstract: To demonstrate the role of oral acyclovir in monthly regimes after microdebrider assisted excision in 3 patients with adult recurrent respiratory papillomatosis (ARRP). Three patients with ARRP who presented to a tertiary referral hospital in stridor were initially treated with a tracheostomy in order to secure airway. On further evaluation by videolaryngoscopy extensive bilateral laryngeal papillomatosis was noted with history of similar conditions in the past for which they were repeatedly operated. They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Evidence from this study suggests that acyclovir has both a safe side effect profile and may be used in combination with surgery as an adjuvant treatment for aggressive RRP 48 . Though robust clinical trials are limited, additional reports endorse these findings and suggest the need for future studies 49 …”
Section: Epidemiological Factorsmentioning
confidence: 62%
“…Evidence from this study suggests that acyclovir has both a safe side effect profile and may be used in combination with surgery as an adjuvant treatment for aggressive RRP 48 . Though robust clinical trials are limited, additional reports endorse these findings and suggest the need for future studies 49 …”
Section: Epidemiological Factorsmentioning
confidence: 62%
“…Chaturvedi et al reports concluded that the action of anti-viral drugs at regular intervals in addition to a short course term of oral steroids led to rapid recovery and prevented latent virus activation within the laryngotracheal system, maintaining long-term improvement. 20 Figure 2. Chest X-ray showing no cavitary or consolidated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…49 It targets herpes simplex virus and Epstein-Barr virus which can be concurrent and coinfection of HPV in RRP. 50 The mechanism of action of acyclovir in RRP is not clear, but it is thought to inhibit DNA viral replication. Acyclovir is used systemically, with dosing in literature ranging from 500-600 mg daily for 5-6 months.…”
Section: Cidofovirmentioning
confidence: 99%